Metastatic Invasive Lobular Carcinoma of the Breast Masquerading as a Primary Renal Malignancy - Al-Jarrah, Adil (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2013)
Breast cancer is known to metastasise to different organs in the body, but an initial presentation of breast cancer with loin pain secondary to a metastatic renal mass is extremely rare. We report a 58-year-old woman who presented with recurrent left loin pain due to a metastatic deposit of invasive lobular carcinoma of the breast. The detection of a renal mass on computed tomography led to the assumption of a renal pelvic malignancy. The diagnostic dilemma posed by the detection of a breast mass during staging and the usefulness of immunohistochemistry in the confirmation of diagnosis are discussed.